If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5(1 + 6X) + -8x = 38 + 5x (1 * -5 + 6X * -5) + -8x = 38 + 5x (-5 + -30X) + -8x = 38 + 5x Solving -5 + -30X + -8x = 38 + 5x Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '5' to each side of the equation. -5 + -30X + 5 + -8x = 38 + 5 + 5x Reorder the terms: -5 + 5 + -30X + -8x = 38 + 5 + 5x Combine like terms: -5 + 5 = 0 0 + -30X + -8x = 38 + 5 + 5x -30X + -8x = 38 + 5 + 5x Combine like terms: 38 + 5 = 43 -30X + -8x = 43 + 5x Add '8x' to each side of the equation. -30X + -8x + 8x = 43 + 5x + 8x Combine like terms: -8x + 8x = 0 -30X + 0 = 43 + 5x + 8x -30X = 43 + 5x + 8x Combine like terms: 5x + 8x = 13x -30X = 43 + 13x Divide each side by '-30'. X = -1.433333333 + -0.4333333333x Simplifying X = -1.433333333 + -0.4333333333x
| 4=2u-2 | | 4i/9-6i | | 0.5p=3.5 | | -x+17+3x+17=-4 | | 3+4y=9 | | 0.25w=16 | | -6k+3=-7-(6k-8) | | 2=2m-2 | | 4x(2x+9)-2(5x+6)= | | 7x+4-3+5-3x= | | 3x-11=-2x-7 | | -16=3-5n+1 | | 18y=6 | | 2*(1200/x) | | 6/m-3 | | 3j-2=14 | | x-6.25=2.5 | | -28x-7y=28 | | 7x+4y-3x+4= | | 13+x(x-13)-(2-5x)=2.8 | | 15d+7=8d+56 | | 19-x=2 | | 3+4j=11 | | -10=-4a-6a | | 3.4=6c-8 | | 2+2r=4 | | 6-2x-1=13 | | 1=5-2t | | 5p=41.5 | | 1.5-0.04x=-0.7 | | 12-5x+5=7-3x+6 | | -48+3x=24-6x |